Negative differential resistance in porous silicon devices at room temperature - Marín Ramírez, Oscar Alonso (2015)
Fil: Marín Ramírez, Oscar Alonso. Universidad Nacional de Tucumán. Facultad de Ciencias Exactas y Tecnología; Argentina.